Kinome Expansion in the Fusarium oxysporum Species Complex Driven by Accessory Chromosomes - Gregory A. DeIulio (American Society for Microbiology, 2018)
ABSTRACT The Fusarium oxysporum species complex (FOSC) is a group of soilborne pathogens causing severe disease in more than 100 plant hosts, while individual strains exhibit strong host specificity. Both chromosome transfer and comparative genomics experiments have demonstrated that lineage-specific (LS) chromosomes contribute to the host-specific pathogenicity. However, little is known about the functional importance of genes encoded in these LS chromosomes. Focusing on signaling transduction, this study compared the kinomes of 12 F. oxysporum isolates, including both plant and human pathogens and 1 nonpathogenic biocontrol strain, with 7 additional publicly available ascomycete genomes. Overall, F. oxysporum kinomes are the largest, facilitated in part by the acquisitions of the LS chromosomes. The comparative study identified 99 kinases that are present in almost all examined fungal genomes, forming the core signaling network of ascomycete fungi. Compared to the conserved ascomycete kinome, the expansion of the F. oxysporum kinome occurs in several kinase families such as histidine kinases that are involved in environmental signal sensing and target of rapamycin (TOR) kinase that mediates cellular responses. Comparative kinome analysis suggests a convergent evolution that shapes individual F. oxysporum isolates with an enhanced and unique capacity for environmental perception and associated downstream responses. IMPORTANCE Isolates of Fusarium oxysporum are adapted to survive a wide range of host and nonhost conditions. In addition, F. oxysporum was recently recognized as the top emerging opportunistic fungal pathogen infecting immunocompromised humans. The sensory and response networks of these fungi undoubtedly play a fundamental role in establishing the adaptability of this group. We have examined the kinomes of 12 F. oxysporum isolates and highlighted kinase families that distinguish F. oxysporum from other fungi, as well as different isolates from one another. The amplification of kinases involved in environmental signal relay and regulating downstream cellular responses clearly sets Fusarium apart from other Ascomycetes. Although the functions of many of these kinases are still unclear, their specific proliferation highlights them as a result of the evolutionary forces that have shaped this species complex and clearly marks them as targets for exploitation in order to combat disease.